COST-EFFECTIVENESS ANALYSIS ON THE USE OF PARENTERAL NUTRITION WITH D10-CA GLUCONATE AND D5 1/4NS IN NORMAL-WEIGHT NEONATES WITH RESPIRATORY DISTRESS SYNDROME - Ningsih, Fitria; Sauriasari, Rani; Saptaningsih, Agusdini Banun (International Journal of Applied Pharmaceutics, 2017)
Objectives: This retrospective cohort study aimed to compare the cost-effectiveness of using D10-CaGluconate and D5 1/4NS preparations in normal weight neonatal patients with Respiratory Distress Syndrome (RDS) in Kambang General Hospital, Jambi, Indonesia. Methods: The research was conducted from September 2014 to June 2015. The study participants were divided into two groups; D10-CaGluconate was administered to 40 patients and D5 1/4NS to 43 patients. Effectiveness was assessed based on the changes in the physical examination results, average weight gain (28.48 and 23.49 g/day), blood glucose levels (26.73 and 26.42 mg/dL), respiratory rate (-12.35 breaths/minute and -7.77 breaths/minute), pulse frequency (-10.98 and -8.07 ±), and body temperature (0.013 °C and 0.012 °C) of the patients in the D10-CaGluconate and D5 1/4NS groups, respectively. Results: The average direct medical costs of using D10-CaGluconate and D5 1/4NS were 458,290 IDR and 408,347 IDR, respectively. The average costeffectiveness ratio value of total direct medical costs for D10-CaGluconate preparation was 35,207,467 IDR while that for D5 1/4NS was 33,958,602 IDR. The direct medical cost of the incremental cost-effectiveness ratio mean value of the D5 1/4NS preparation that compared to the D10-CaGluconate preparation was 10,017,210 IDR. Conclusions: The parenteral nutrition preparation of D10-CaGluconate is more cost-effective than that of D5 1/4NS.